Peripheral Nerve Block Provides Effective Analgesia for a Patient With Peripheral Nerve Hyperexcitability Syndrome: Isaacs Syndrome Case Report. Issue 10 (15th November 2018) - Asai, Akinori; Kako, Eisuke; Hasegawa, Tatsuya; Sobue, Kazuya
Abstract : Isaacs syndrome is a rare peripheral nerve hyperexcitability syndrome. The painful discharges in Isaacs syndrome are abolished by the blockade of the neuromuscular junction but not by peripheral nerve blocks (PNB). However, the efficacy of PNB for intraoperative and postoperative analgesia among those with Isaacs syndrome is unknown. A 41-year-old woman with Isaacs syndrome underwent open reduction and internal fixation of radius fractures. Ultrasound-guided bilateral axillary brachial plexus blocks were performed, followed by general anesthesia. The patient required only a single low dose of rocuronium for intubation and surgery. On emergence from anesthesia, the patient was pain free for 6 hours and did not return to her preoperative pain state for 36 hours. PNB can be an effective means of postoperative pain control for patients with Isaacs syndrome.